Industry Dynamics and Entrepreneurship: An Equilibrium Model - Dennis Fok; Andre van Stel; Andrew Burke; Roy Thurik (Tinbergen Institute, 2010)
This paper conducts the first general equilibrium analysis of the role of entry, exit and profits in industry dynamics. The benefit of our model is twofold. First, to discriminate between entrants' role of performing the entrepreneurial function of creating disequilibrium and the conventional equilibrating role of moving the industry to a new equilibrium. Second, to discriminate between three aspects of industry dynamics: the effect of entry and exit on market equilibrium, duration of disequilibrium and patterns of adjustment. Using a rich data set of the retail industry, we construct a dynamic simultaneous equilibrium model of profits, entry and exit. We find that indeed entrants play an entrepreneurial function causing long periods of disequilibrium after which a new equilibrium is attained. Moreover, we find ample support for the statement that disequilibrium is the essence of economic progress.
Keywords: B50; J01; L00; L1; L26; 330; entry; exit; profits; equilibrium; industrial dynamics; retailing; Industrieproduktion; Markteintritt; Marktaustritt; Entrepreneurship-Ansatz; Allgemeines Gleichgewicht; Schätzung; Niederlande